Enhancing Psychological Well-Being Assessment Through Data Mining: A Case Study from Thailand - Asamaporn Treearpornwong; Thiyaporn Kantathanawat; Mai Charoentham; Paitoon Pimdee; Aukkapong Sukkamart (European Journal of Investigation in Health Psychology and Education, 2025)
This study examines the psychological well-being (PWB) of lower secondary school students in Bangkok's Secondary Educational Service Area Offices (SESAO) 1 and 2, using data mining techniques to analyze key influencing factors and develop a culturally adapted PWB questionnaire. The research framework is based on six components: autonomy, environmental mastery, personal growth, positive relationships, life purpose, and self-acceptance. Data were collected from 2543 students in the 2023 academic year and analyzed using the Waikato Environment for Knowledge Analysis (WEKA) program and the JRip rule-based classification model. Results indicate that personal growth is the most predictive in the classification performance of PWB, followed by positive relationships and life purpose. A newly developed PWB questionnaire was tested for reliability, with the Supplied Test Set (80:20) method yielding strong performance metrics, including accuracy (90.18%), precision (69.00%), recall (90.90%), and F-measure (78.40%). This study demonstrates data mining's effectiveness in identifying factors influencing adolescent PWB within the Thai context. The findings provide educators and policymakers with insights for fostering student well-being and contribute to research by offering a validated, culturally relevant assessment tool.
Keywords: Psychological Well-being and Life Satisfaction; Obesity, Physical Activity, Diet; Grit, Self-Efficacy, and Motivation